Viral vector-mediated expressions of venom peptides as novel gene therapy for anxiety and depression. (September 2022) - Okada, Masayoshi; Ortiz, Ernesto
Abstract: The venoms of arachnids, cone snails, and snakes consist of many peptides that have various physiological activities, e.g., modulation of ion channels. We have recently prepared lentiviral vectors that express spider venom peptides and observed their successful expression and secretion by the transduced cells themselves. We expect that this expression method can be applied to mental disorders as a new type of gene therapy. Since most psychiatric symptoms are caused by dysregulations of neuronal activities and/or synaptic transmission, a single injection of a viral vector that expresses venom peptides would modulate ion channels in the brain and thereby compensate for the dysregulations, resulting in long-lasting therapeutic potential. Here, we discuss the details of the application methods and which venom peptide would exert therapeutic effect for anxiety and depression and how.